Effect of Financial Ratios, Macroeconomics, and Corporate Governance on Financial Distress - Nursal, Ehla Zakiyah; Kristanti, Farida Titik; Murti, Galuh Tresna (Asean International Journal of Business, 2023)
This study aims to investigate activity ratios, sales growth, operating cash flow, investment cash flow, funding cash flow, rupiah exchange rate, CEO gender, and financial distress in non-primary consumer companies listed on the Indonesia Stock Exchange in the 2014-2021 period. Methodology/approach – This research is a quantitative research. The sampling technique in this study used purposive sampling. The population in this study amounted to 56 companies. The data analysis method used in this study is survival analysis. Findings – The results of the study show that activity ratios and sales growth have a significant effect on financial distress, while operating cash flow, investment cash flow, financing cash flow, exchange rate and gender of the CEO have no effect on financial distress. Novelty/value –  This research uses non-primary consumer sector companies that only take effect on January 25, 2021 on the Indonesia Stock Exchange. And survival analysis with cox proportional hazard as a regression method, where this method is rarely used in research.